(untitled) (Anwer Khan Modern Medical College Journal, 2012)
The most common nosocomial infection is Urinary tract infection (UTI) among hospitalized patients as well as UTI is an important health problem in the community. The knowledge about the type of pathogens responsible for UTI and at a specific area may help the doctors to choose correct treatment regimen. This study was aimedat to investigate the pattern of isolated urinary pathogens. This study was done at Anwer Khan Modern Medical College Hospital, Dhaka during January- June, 2011. Out of 498 clinical samples of urine collected, 245 (49.19%) showed significant bacterial growth. The most common pathogens isolated were Escherichia coli (142, 58.0%), Streptococcus feacalis (38, 15.5%), Pseudomonus (20, 8.2%), Klebsiella species (20, 8.2%) and Staphylococcus epidermidis (14, 5.7%). The clinicians should use antibiotics according to pattern of causative agents that cause UTI in such setting. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10107 AKMMCJ 2012; 3(1): 13-15